Use of participatory forum theatre to explore HIV/AIDS issues in the workplace (Communicare: Journal for Communication Studies in Africa, 2022)
The continued success of entertainment education programmes around the world has seen anincrease in the use of theatre for HIV/AIDS interventions. Both UNAIDS and UNESCO recommendthe use of such cultural strategies for HIV/AIDS awareness. A brief survey of current evaluationsin this field reveals such projects in Kenya, Angola, Mozambique, the Netherlands and Honduras,amongst other countries. Forum theatre is reported as being used as a technique to deepenunderstanding of HIV/AIDS issues in programmes in Georgia, Tanzania, Burkina Faso and SouthAfrica (The Communication Initiative, 2007).This paper explores the application of participatory theatre techniques in a South African factoryenvironment in 2003. It investigates the conditions and context for the project, some of the theoreticalunderpinnings of the forum theatre concept, and the reception of the project by the factory audience.Essentially, the paper seeks to determine whether forum theatre is an appropriate strategy to usefor HIV/AIDS awareness in this environment.